Nickel-Сatalyzed Carbon–Selenium Bond Formations under Mild Conditions - Zhumagazy, Serik; Zhu, Chen; Yue, Huifeng; Rueping, Magnus (Synlett, 2023)
A nickel-catalyzed C–Se cross-coupling between aryl iodides and selenols is described. The newly developed catalytic methodology offers facile access to various unsymmetrical selenium-containing motifs. The reaction features excellent functional group tolerance, wide substrate scope, good efficiency, and operates under mild reaction conditions. Notably, this protocol could be readily scaled up to gram scale without the loss of yield.
Keywords: nickel catalysis; C–Se bond formation; aryl halide; cross-coupling